The Impact of Nurturing Talent in A Science, Engineering and Technology Programme on Learner Performance in Physical Science (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2022)
This paper investigated the impact of the Nurturing talent in Science, Engineering and Technology (NSET) programme on teaching practices in rural schools within the Nkowankowa cluster in the Limpopo Province. Though NSET programme focused on Science, Mathematics and Technology, this study will only concentrate on Physical Sciences. Out of the population of 68 Science teachers, 30 participated in the completion of questionnaires and nine were interviewed. A mixed-methods approach with an exploratory design was used in this study to investigate the impact of the NSET programme on learner performance in Physical Sciences (focusing on teacher content and pedagogical delivery). For learners to consistently perform better, then one need to focus on teacher development in terms of content and pedagogy. The model that focuses on teacher development in order to address the performance of learners helps to sustain better results at school than focusing directly on learners since the teachers are likely to interact with more learners and stay at the same school longer. Questionnaires, interviews and document analysis were used as data collection methods. According to the research findings, the NSET programme had a positive impact on both the content and pedagogical delivery of teachers. This was revealed through the confidence educators gained and their ability to come up with new teaching strategies and improved teaching practices. The positive impact of the NSET programme is also noted through learners’ improved academic performance in Physical Science. The NSET programme conducted within the Nkowankowa cluster yielded positive results and the Limpopo Department of Basic Education (DBE) can adopt it as one of the best practices in the development of teachers and improvement of results in their schools.